2003
DOI: 10.1097/00008571-200305000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Novel paraoxonase (PON1) nonsense and missense mutations predicted by functional genomic assay of PON1 status

Abstract: Paraoxonase (PON1) has been termed an environmental response enzyme for its function in the detoxification of organophosphate pesticides, nerve agents and pharmaceuticals such as glucocorticoids and statins, as well as its cardioprotective role in breaking down oxidized LDL. PON1(192) genotype can be predicted with high accuracy from an examination of the two-dimensional plot of paraoxon and diazoxon hydrolysis rates [ 1]. Individuals for whom this functional genomic assay failed to predict PON1(192) genotype,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 11 publications
4
65
0
Order By: Relevance
“…Diazoxonase activity versus paraoxonase (PONase) activity (upper plot) and chlorpyrifosoxonase (CPOase) activity versus PONase activity (lower plot) for chlorpyrifos subjects (filled symbols) and referent subjects (open symbols). Inferred genotypes were derived from the clustering observed in the diazoxonase versus PONase plot (Furlong et al, 2000b;Jarvik et al, 2003).…”
Section: Results Of Linear Regression Modelsmentioning
confidence: 99%
“…Diazoxonase activity versus paraoxonase (PONase) activity (upper plot) and chlorpyrifosoxonase (CPOase) activity versus PONase activity (lower plot) for chlorpyrifos subjects (filled symbols) and referent subjects (open symbols). Inferred genotypes were derived from the clustering observed in the diazoxonase versus PONase plot (Furlong et al, 2000b;Jarvik et al, 2003).…”
Section: Results Of Linear Regression Modelsmentioning
confidence: 99%
“…Arylase was measured in triplicate. The plot of POase versus DZOase accurately predicts PON1 192 genotype in both cases and controls; this plot was used to fill in three missing genotypes (39).…”
Section: Pon1 Genotype and Activity Measuresmentioning
confidence: 99%
“…Human clinical studies suggest that PON1 phenotype, i.e., paraoxonase activity is a much stronger predictor of cardiovascular disease status than PON1 genetic polymorphisms [51][52][53][54][55] a finding that has been confirmed in other studies [52,55]. Bhattacharyya and colleagues demonstrated that both the pon1 Q192R polymorphism and serum PON1 activity are associated with prevalent coronary artery disease and incident adverse cardiovascular events [56].…”
Section: Pon1 Variants and Oxidative Stress-related Disordersmentioning
confidence: 90%